2017
DOI: 10.4103/jrms.jrms_976_16
|View full text |Cite
|
Sign up to set email alerts
|

Diverse pattern of gap junction beta-2 and gap junction beta-4 genes mutations and lack of contribution of DFNB21, DFNB24, DFNB29, and DFNB42 loci in autosomal recessive nonsyndromic hearing loss patients in Hormozgan, Iran

Abstract: Background:We aimed to determine the contribution of four DFNB loci and mutation analysis of gap junction beta-2 (GJB2) and GJB4 genes in autosomal recessive nonsyndromic hearing loss (ARNSHL) in South of Iran.Materials and Methods:A total of 36 large ARNSHL pedigrees with at least two affected subjects were enrolled in the current study. The GJB2 and GJB4 genes mutations were screened using direct sequencing method. The GJB2 and GJB4 negative families were analyzed for the linkage to DFNB21, DFNB24, DFNB29, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The current study found that 25-hydroxyvitamin D levels were inversely correlated with glycemic control measured by HbA1c levels. This finding is consistent with a number of previous research studies 18,23,25. Additionally, the current study found that glycemic control is independently associated with VDD.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The current study found that 25-hydroxyvitamin D levels were inversely correlated with glycemic control measured by HbA1c levels. This finding is consistent with a number of previous research studies 18,23,25. Additionally, the current study found that glycemic control is independently associated with VDD.…”
Section: Discussionsupporting
confidence: 94%
“…According to the American Diabetic Association, HbA1c <7% is the optimal glycemic control 22. It has been suggested that VDD is associated with glycemic control in T2DM 23. However, the role of VDD in glycemic control is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recent decades have seen an increasing interest in the effect of traditional Chinese medicine and its active ingredients on atherosclerosis-related diseases. 21 Isoborneol is a chemical component often found in traditional Chinese medicines, especially those used for the treatment of cardiovascular disease. This study not only provides a new molecular template for the treatment of atherosclerosis but also provides a basis for the treatment of cardiovascular disease using these traditional prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure was monitored at all study visits, using an Omron BP 742 monitor. To calculate ankle-brachial indexes (ABIs), blood pressures were taken on both right and left arms, and on both legs above the ankle such that the bottom edge of the blood pressure cuff was two inches above the lateral malleolus bone 39,40…”
Section: Methodsmentioning
confidence: 99%